Enhancement of machining performance during electrical discharge machining of stainless steel with carbon nanotube powder added dielectric fluid - Khan, Ahsan Ali; Mohiuddin, A. K. M.; Al Hazza, Muataz Hazza Faizi; Norhamzan, Norainnatul Husna (Research India Publications, 2018)
Electrical discharge machining (EDM) is a nontraditional process of removing material from an electrically conductive work piece. It produces sparks to produce any desired shape cavity or geometry. The demand for good surface finish of a workpiece in EDM has developed a new method to improve surface condition where powder material is added to dielectric fluid during EDM. The present paper is on investigation of influence of carbon nanotube (CNT) powder addition to dielectric fluid on EDM performance. The effect of the addition of CNT is analyzed on MRR and surface roughness (Ra). The variable factors were pulse on time (Ton) and powder concentration. The addition of CNT powder has improved the surface roughness and MRR in comparison EDM without CNT addition. Lowest surface roughness obtained by the lowest Ton time of 6μs with the CNT powder concentration of 0.3 mg/L of 8.61μm compared to 9.97μm of no powder addition. Ton of 10μs has produced the highest surface roughness with no powder addition with the value of 30.38μm. The addition of 0.3mg/L powder addition and 10μs Ton enhanced the surface roughness to 29.40μm. The addition of CNT powder with the concentration of 0.3mg/L has also increased the MRR to the highest value of 0.4625g/min from 0.3503g/min without powder addition. The analysis of the result has shown that the MRR and surface finish improved due to CNT powder addition to dielectric.